1998
DOI: 10.1002/jlb.63.3.288
|View full text |Cite
|
Sign up to set email alerts
|

Increased P-selectin gene expression in the liver vasculature and its role in the pathophysiology of neutrophil-induced liver injury in murine endotoxin shock

Abstract: We studied the role of P-selectin, an adhesion molecule known to be important for neutrophil localization to sites of inflammation, in a model of inflammatory liver injury. Male C3Heb/ FeJ (ET-sensitive) mice treated with 700 mg/kg galactosamine and 100 g/kg Salmonella abortus equi endotoxin (Gal/ET), murine tumor necrosis factor ␣ (TNF-␣, 15 g/kg), or interleukin-1 (IL-1, 13-23 g/kg), showed increased P-selectin mRNA levels in the liver. In contrast, C3H/HeJ (ET-resistant) mice responded only to cytokines wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

10
158
2
1

Year Published

1998
1998
2012
2012

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 132 publications
(171 citation statements)
references
References 65 publications
10
158
2
1
Order By: Relevance
“…7 Finally, despite the reduction in venular recruitment, ␣ 4 -integrin-antibody treatment had absolutely no impact on the number of stationary leukocytes in the sinusoids. Essani et al 35 have shown that despite an increase in VCAM-1 expression on sinusoidal endothelium and Kupffer cells in response to endotoxin stimulation (associated with increased ␣ 4 -integrin expression on circulating neutrophils), blocking VCAM-1 had no effect on the number of leukocytes accumulated in the sinusoids. 33 Although this latter study could be explained by the potential recruitment via selectins, our work extends this view to suggest that no known tethering molecules (selectins or ␣ 4 -integrin) play a dominant role in the liver sinusoids.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…7 Finally, despite the reduction in venular recruitment, ␣ 4 -integrin-antibody treatment had absolutely no impact on the number of stationary leukocytes in the sinusoids. Essani et al 35 have shown that despite an increase in VCAM-1 expression on sinusoidal endothelium and Kupffer cells in response to endotoxin stimulation (associated with increased ␣ 4 -integrin expression on circulating neutrophils), blocking VCAM-1 had no effect on the number of leukocytes accumulated in the sinusoids. 33 Although this latter study could be explained by the potential recruitment via selectins, our work extends this view to suggest that no known tethering molecules (selectins or ␣ 4 -integrin) play a dominant role in the liver sinusoids.…”
Section: Discussionmentioning
confidence: 99%
“…This concentration of TNF has been shown to increase P-selectin expression in the portal and central venules of the liver. 6 The TNF-␣ response was first compared between the wild-type animals and mice deficient in P-selectin. In another set of P-selectindeficient animals, a baseline recording was made and the animal was injected with an anti-E-selectin antibody (Ab) (9A9, 100 µg intravenously [IV]) (a gift from Dr. B. Wolitsky).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…7-9 Increased quantities of soluble circulating adhesion molecules have also been detected in various models of liver injury. 2,7,8,10 These findings, together with the observation that liver injury is abrogated by administration of antibodies to certain cell adhesion molecules, [4][5][6]11 suggest that they play a role in hepatotoxicity associated with inflammation.Endotoxin is a bacterially derived product known to induce liver injury at toxic doses. 12 We have previously demonstrated that acute endotoxemia is associated with an increase in the number of macrophages in the liver.…”
mentioning
confidence: 98%
“…Cell adhesion molecules are a group of membraneassociated proteins present on leukocytes, endothelial cells, and parenchymal cells that facilitate monocyte adherence and emigration out of the blood and into the tissue. Expression of several different classes of cell adhesion molecules have been reported to be up-regulated on liver cells after exposure of animals to hepatotoxic doses of alcohol 1,2 or endotoxin, 3,4 following reperfusion injury, 5,6 and in humans with acute and chronic inflammatory liver diseases. [7][8][9] Increased quantities of soluble circulating adhesion molecules have also been detected in various models of liver injury.…”
mentioning
confidence: 99%